PENGARUH PENYULUHAN TENTANG PEMANFAATAN JAMBAN TERHADAP PERILAKU BUANG AIR BESAR YANG SEHAT - Ridwan, Ahmad; Fradana, Fendi (Jurnal AKP, 2013)
Family latrine is a building used to dispose of faeces or human excrement to a family commonly known as (WC). The purpose of this study is to investigate the influence of education on the use of latrines to the behavior of healthy bowel on RT 01 RW 01 Desa Dusun Ngrangkok Klampisan Kandangan Kediri District Year 2011.The research design will be used in this research is to design research at the level of pre-experimental design precisely on-one-group pre-post test design, the population of 30 heads of families who were taken with a purposive sampling technique sampling contained 23 samples with the inclusion criteria. By analysis using Wilcoxon test through the help of computer software. Results obtained from 23 respondents, the vast majority behave defecate qualify after the extension that is 10 respondents (43,48%) and the smallest is not eligible ie there are 8 respondents (34,78%). The test results using Wilcoxon tests with the result P value: 0.001 <0.05. Thus p <Â  then working hypothesis (H1) was accepted and nil hypothesis (Ho) is rejected it means there is the influence of education on the use of latrines to the behavior of a healthy bowel movement. This is because education is a component that affects the behavior of the family. The more often get the better education also behavior in everyday life. For that family needs to get a good education from the health department or from health workers about the behavior of proper bowel movements. Â Keywords: Counseling, Utilization Latrines, Behavior